2002
DOI: 10.1074/jbc.m206624200
|View full text |Cite
|
Sign up to set email alerts
|

Yeast Cells Lacking the ARV1 Gene Harbor Defects in Sphingolipid Metabolism

Abstract: ]dihydrosphingosine radiolabeling studies demonstrated that mutant cells had reduced rates of biosynthesis and lower steadystate levels of complex sphingolipids while accumulating certain hydroxylated ceramide species. Phospholipid radiolabeling studies showed that arv1⌬ cells harbored defects in the rates of biosynthesis and steadystate levels of phosphatidylcholine, phosphatidylethanolamine, phosphatidylserine, and phosphatidylglycerol. Neutral lipid radiolabeling studies indicated that the rate of biosynthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
68
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(72 citation statements)
references
References 77 publications
4
68
0
Order By: Relevance
“…The genes for the two proteins share synthetic genetic and chemical genetic interactions (40): synthetic lethality between erg11 and arv1 strains and hypersensitivity of the arv1 strain to fluconoazole, an antimicrobial compound that targets Erg11. Yeast lacking Arv1 are defective in sphingolipid and sterol metabolism (41) and accumulate lanosterol, the substrate that Erg11 demethylates in the course of ergosterol biosynthesis (42). The identified interaction between these proteins may connect their functions in ergosterol metabolism.…”
Section: Resultsmentioning
confidence: 99%
“…The genes for the two proteins share synthetic genetic and chemical genetic interactions (40): synthetic lethality between erg11 and arv1 strains and hypersensitivity of the arv1 strain to fluconoazole, an antimicrobial compound that targets Erg11. Yeast lacking Arv1 are defective in sphingolipid and sterol metabolism (41) and accumulate lanosterol, the substrate that Erg11 demethylates in the course of ergosterol biosynthesis (42). The identified interaction between these proteins may connect their functions in ergosterol metabolism.…”
Section: Resultsmentioning
confidence: 99%
“…arv1 cells harbor defects in sphingolipid and GPI synthesis, and although their overall sterol content is normal, our data, as well as that of others, strongly suggest these lipids are trafficked improperly and thus are mislocalized (Tinkelenberg et al 2000;Swain et al 2002;Fei et al 2008;Kajiwara et al 2008). Membrane microdomains, also known as lipid rafts, are sphingolipidand sterol-rich regions of the plasma membrane, which are capable of mediating membrane sorting, cell adhesion, and signal transduction (Harder et al 1998).…”
Section: Discussionmentioning
confidence: 78%
“…In addition to having defects in sphingolipid and GPI syntheses, arv1 cells harbor defects in phospholipid biosynthesis and metabolism (Swain et al 2002). Ste5 has an N-terminal amphipathic a-helix, which is important for nuclear localization and membrane binding (Winters et al 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that ergosterol levels affect the amounts of certain sphingolipid species (45). Moreover, ⌬arv1 cells, in which intracellular sterol distribution is altered, also harbor defects in sphingolipid synthesis (46). Thus, there seems to be unknown mechanisms that regulate sphingolipid synthesis in response to cellular ergosterol status.…”
Section: Discussionmentioning
confidence: 99%